2011
DOI: 10.1002/glia.21246
|View full text |Cite
|
Sign up to set email alerts
|

Glucose increases intracellular free Ca2+ in tanycytes via ATP released through connexin 43 hemichannels

Abstract: The ventromedial hypothalamus is involved in regulating feeding and satiety behavior, and its neurons interact with specialized ependymal-glial cells, termed tanycytes. The latter express glucose-sensing proteins, including glucose transporter 2, glucokinase and ATP-sensitive K+ (KATP) channels, suggesting their involvement in hypothalamic glucosensing. Here, the transduction mechanism involved in the glucose-induced rise of intracellular free Ca2+ concentration ([Ca2+]i) in cultured β-tanycytes was examined. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
191
0
3

Year Published

2012
2012
2017
2017

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 162 publications
(207 citation statements)
references
References 49 publications
13
191
0
3
Order By: Relevance
“…These findings are in line with growing literature showing that hypothalamic glial cells are involved in central glucose sensing and action (25)(26)(27)(28)(29). It is important to mention that we did not observe an increase in palmitate oxidation in response to AICAR in cortical astrocytes.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…These findings are in line with growing literature showing that hypothalamic glial cells are involved in central glucose sensing and action (25)(26)(27)(28)(29). It is important to mention that we did not observe an increase in palmitate oxidation in response to AICAR in cortical astrocytes.…”
Section: Discussionsupporting
confidence: 93%
“…Hypothalamic neurons (24) and glia (25)(26)(27)(28)(29) are both able to sense glucose, and the importance of astroglia in central nutrient sensing has been recently emphasized (30). It is unclear if glucose modulation of LCFACoA metabolism occurs in neurons and/or astrocytes and whether or not such a feature distinguishes hypothalamic nuclei from other brain regions.…”
mentioning
confidence: 99%
“…Tanycytes play a major role in the formation of the median eminence-cerebrospinal fl uid barrier ( Figure 2E). More recently, these cells have been found to be crucial for the brain glucose sensing mechanism (Cortes-Campos et al, 2011;Orellana et al, 2012).…”
Section: Stem Cells During Brain Development and Adult Lifementioning
confidence: 99%
“…Therefore, the presence of MCT1 and MCT4 in tanycytic basal processes and MCT2 expression in AN neurons suggest that lactate could be transferred between both cellular types as a signal derived from glucose for regulating energy balance and food intake. In support of this model, it has been demonstrated that glucose increases intracellular Ca 2+ concentration ([Ca 2+ ] i ) in cultured tanycytes, a response that is oxidative phosphorylation-independent but can be diminished through the inhibition of glucokinase, a critical glucosensor enzyme expressed in tanycytes [32][33][34]. Interestingly, this mechanism involves the opening of hemi channels (HC), and pharmacological inhibitors of HC abolish the response to glucose, but do not affect the efflux of lactate [6,33,35].…”
Section: Introductionmentioning
confidence: 96%
“…In support of this model, it has been demonstrated that glucose increases intracellular Ca 2+ concentration ([Ca 2+ ] i ) in cultured tanycytes, a response that is oxidative phosphorylation-independent but can be diminished through the inhibition of glucokinase, a critical glucosensor enzyme expressed in tanycytes [32][33][34]. Interestingly, this mechanism involves the opening of hemi channels (HC), and pharmacological inhibitors of HC abolish the response to glucose, but do not affect the efflux of lactate [6,33,35]. Several studies have shown that ICV administration of lactate decreases food intake and stimulates pancreatic insulin secretion [36,37].…”
Section: Introductionmentioning
confidence: 96%